Analisis Struktur dan Nilai Budaya dalam Cerita Rakyat Palembang - Devi Tri Utami; Kirani Kirani; Izzah Izzah; Raka Gunaika (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2026)
This study aims to analyze the story structure and uncover the cultural values contained in Palembang folktales. The study uses a qualitative approach with descriptive analysis methods. The data sources are several folktales that have developed in the Palembang community, obtained through documentation and literature studies. The analysis is carried out by examining elements of story structure such as theme, plot, characters and characterization, setting, and moral, then identifying the cultural values reflected in the stories. The results show that Palembang folktales have a relatively simple narrative structure but are strong in conveying moral messages. In addition, various cultural values were found that are still relevant to community life, such as the values of togetherness, respect for parents, local wisdom, honesty, hard work, and the relationship between humans and nature and their social environment. These values indicate that folktales function not only as entertainment, but also as a means of cultural inheritance and character formation in society. This research is expected to enrich the study of regional literature and become learning materials in education, especially in learning Indonesian.